OPTIMIZATION OF PORTFOLIO FOR MEAN VARIANCE RISK MEASURE WITH MULTI OBJECTIVE APPROACH USING ANT COLONY METHOD - Septriani, Nicke
The two most important things in portfolio optimization are minimizing risk and maximizing return. Of course, it would be more interesting if the return and risks can be optimized simultaneously, this problem is known as multi-objective portfolio problem. The optimization model that is often used to solve this portfolio optimization problem is the mean-variance. This model is made on the mean and variance approach. Constraints that often arise are buy-in threshold, cardinality, and roundlot. The method used for the problem of portfolio optimization in this thesis is by using Ant Colony method by conducting Rastrigin, Grewank, and Rosenbrock. Furthermore, the Ant Colony method is used for single objective optimization. Then for a multi-objective approach using data 50 Hang Seng stocks and 45 shares of LQ45. The multi objective optimization result also displays the front pareto for each taking K = 5,10,15 shares of available n- stock. The tool used for this Ant Colony method is MATLAB2015a.